2005
DOI: 10.1248/bpb.28.2080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Vitamin E and Insulin Administration on Renal Damage in Diabetic Rats Fed a High Cholesterol Diet

Abstract: Diabetic nephropathy is characterized by persistent proteinuria, hypertension and declining renal function. Microalbuminuria is detected at the early stage of diabetic nephropathy. Approximately 30-40% of type 1 diabetic patients have renal complications, which are a major cause of mortality.1-3) Diabetes mellitus is a disease characterized by hyperglycemia. On the other hand, hyperlipidemia in addition to hyperglycemia has been frequently observed in insulin-dependent 4,5) and non-insulin-dependent diabetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Free radical production and decreased endogenous antioxidant defenses during DM are also directly related to micro-and macrovascular alterations (e.g., atherosclerosis) considered to be the main causes of morbidity and mortality in diabetic patients (Son 2007). The enzymes hepatic superoxide dismutase, catalase, and glutathione peroxidase are examples of endogenous antioxidants that are decreased in experimental models of streptozotocin-induced DM (Yoshida et al 2005). Several mechanisms appear to be involved in the genesis of oxidative stress in diabetes in animals and humans (type 1 and type 2 diabetic patients), including glucose autoxidation, protein glycation, advanced glycation endproduct formation, and the poliol pathway (Bonnefont-Rousselot et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free radical production and decreased endogenous antioxidant defenses during DM are also directly related to micro-and macrovascular alterations (e.g., atherosclerosis) considered to be the main causes of morbidity and mortality in diabetic patients (Son 2007). The enzymes hepatic superoxide dismutase, catalase, and glutathione peroxidase are examples of endogenous antioxidants that are decreased in experimental models of streptozotocin-induced DM (Yoshida et al 2005). Several mechanisms appear to be involved in the genesis of oxidative stress in diabetes in animals and humans (type 1 and type 2 diabetic patients), including glucose autoxidation, protein glycation, advanced glycation endproduct formation, and the poliol pathway (Bonnefont-Rousselot et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E interferes with the process of lipid peroxidation, protecting polyunsaturated fatty acids against attack by free radicals (Yoshida et al 2005). The presence of vitamin E in neuronal cells membranes, especially the inner mitochondrial membrane, suggests its possible use in the treatment of DM.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been reported that diabetic rats treated with insulin show normalized lipid levels (Yoshida, M., et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that water soluble portion of alcoholic extract of leaves of Azadirachtaindicapossesses significant antiinflammatory, antiserotonin,antifertility and hepatoprotective activity (Ravi, K., et al, 2004;Sekar, D.S., et al, 2005;Sharma, S.B., et al, 2003;Yehuda, et al, 2005;Sukla, R., et al, 1973;Xin, et al, 2012;Yoshida, M., et al, 2005;Zimmer, Carl., 2015;Van Dam, R.M., et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vitamin E interferes with lipid peroxidation and inhibits the enzyme phospholipase A2, thus preventing membrane phospholipid hydrolysis (15,31,36,43,45) . The present study investigated the effects of vitamin E supplementation at different concentrations (0.1% and 2%) on the general population of myenteric neurons (myosin-V-immunoreactive) and on the subpopulation of nitrergic neurons (neuronal nitric oxide synthase [nNOS]-immunoreactive) in the jejunum of rats with DM.…”
Section: Supplementation With 01% and 2% Vitamin E In Diabetic Rats:mentioning
confidence: 99%